Perkembangan Kurikulum Di Lembaga Pendidikan Madrasah Sebagai Upaya Integrasi Keilmuan : Sebuah Tinjauan Historis - Indah Dina Pratiwi (STAI Tebing Tinggi Deli, 2019)
Madrasa becomes a place or institution that is always identified with Islamic education.An irony, when today's society always identifies that the madrasa merely runs thereligious science curriculum, and overrides general science and / or science. Eventhough in its historical period, there has been a real dichotomy of knowledge in theIslamic world which resulted in the decline of Islamic education after the generaleducation curriculum was kicked from Islamic educational institutions around the 12-13th century AD.In the study of Islamic education philosophy, the curriculum is identified with manhaj,which is a clear path that must be passed so that the goal of Islamic education can beachieved, which is to form a perfect human being. For this reason, it is imperative thatIslamic educational institutions must transform with the current developments. Likewise,madrasa educational institutions. The curriculum in madrasas must be able to integratethe religious sciences with modern science